Energy and environment - Loulou, Richard (Springer, 2014)
A work on energy and environmental modeling that describes a broad variety of modeling methodologies, embodied in models of varying scopes and philosophies. It includes examples that range from top-down integrated assessment models to bottom-up partial equilibrium models, to hybrid models.